2019
DOI: 10.1530/rep-18-0449
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation in the pathogenesis of polycystic ovary syndrome

Abstract: Polycystic ovary syndrome (PCOS) is the leading endocrine and metabolic disorder in premenopausal women characterized by hyperandrogenism and abnormal development of ovarian follicles. To date, the PCOS etiology remains unclear and has been related to insulin resistance, obesity, type 2 diabetes mellitus, cardiovascular disease and infertility, among other morbidities. Substantial evidence illustrates the impact of genetic, intrauterine and environmental factors on the PCOS etiology. Lately, epigenetic factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(51 citation statements)
references
References 116 publications
2
43
0
Order By: Relevance
“…A total of 33 PCOS ladies (mean age 26.8, range [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] were enrolled between June 2017 and October 2018, and one patient withdrew her participation for personal reasons after the basal visit. Out of 32 patients randomized, 22 entered the active treatment group, and 10 the no treatment group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 33 PCOS ladies (mean age 26.8, range [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] were enrolled between June 2017 and October 2018, and one patient withdrew her participation for personal reasons after the basal visit. Out of 32 patients randomized, 22 entered the active treatment group, and 10 the no treatment group.…”
Section: Resultsmentioning
confidence: 99%
“…Assumed that a multiple micronutrient support is effective in reducing Hcy, whether or not a Hcy lowering treatment should be offered to PCOS ladies remains a controversial question. The function of the one carbon metabolism is deranged in PCOS possibly resulting in impaired mitochondrial activity [30] and the resulting abnormal DNA methylation and epigenetics may contribute to the pathogenesis of the disease [31], which could be a strong reason to correct HHcy in any PCOS patient. Moreover, Hcy is a well-known risk factor for cardiovascular disease [13,32] that is a main co-morbidity of PCOS [33], hence a preventive treatment may be indicated.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with these findings and the well-established, androgen receptor-mediated, elongation of the anogenital distance (AGD) as an initial component of genital virilization, newborn daughters of women with PCOS [29], as well as adult PCOS women [59][60][61], exhibit elongated AGDs. Differential patterns of DNA methylation in newborn girls of PCOS women [52], as well as in adult PCOS women themselves [26,62,63], implicate epigenetic modifications during a critical developmental window, potentially indicative of changes in degree of individual gene expression.…”
Section: The Evidence For Developmental Origins Of Pcos From Clinicalmentioning
confidence: 99%
“…For example, studies of obese women two years after weight loss gastric bypass surgery revealed differential methylation of adipogenic genes, which may contribute to resistance to weight loss 46 . Furthermore, altered DNA methylation in genes involved in inflammation and glucose and lipid metabolism has been reported in peripheral and umbilical cord blood, as well as in various tissues of women with PCOS 47 . However, relatively few studies to date have addressed DNA methylation changes in WAT of women with PCOS 40,42,43 .…”
Section: Introductionmentioning
confidence: 99%